Improvement of lifting mechanism of an intelligent additional track system for a Swamppeat tracked vehicle - Iqbal A.K.M.P.; Zabri N.H.M.; Begum S.; Aris I.B. (Medwell Journals, 2023)
This study presents the improvement of lifting mechanism of an intelligent additional track system for a tracked vehicle. The lifting mechanism is attached to the additional track system at the middle frame of tracked vehicle. It is used to lift the additional track system upwards and downwards depend on the condition of ground surface. In previous study, a tracked vehicle with an intelligent additional track mechanism has been developed to full fill the demand of swamp peat vehicle. However, the design of link mechanism is used to move the additional track is not effectively functioning as it causes the delay and misalignment during the operation. Hence, four different concepts would be generated through morphological method in order to find a proper link mechanism. For each concept, there would be different prospects and functions of their own. Those concepts would be illustrated in design sketches and simulated through morphological diagram. Finally, the best model would be chosen and analysed. Medwell Journals, 2017.